Firearm Purchasing During the COVID-19 Pandemic: Results From the 2021 National Firearms Survey - Miller, Matthew; Zhang, Wilson; Azrael, Deborah (Annals of internal medicine, 2022)
The surge in background checks beginning in March 2020 suggested an acceleration in firearm purchases. Little was known about the people who bought these guns. To estimate the number and describe characteristics of firearm purchasers over a period spanning prepandemic and pandemic time, characterize new gun owners, and estimate the number of persons newly exposed to household firearms. Probability-based online survey conducted in April 2021. Survey weights generated nationally representative estimates. United States, 1 January 2019 to 26 April 2021. 19 049 of 29 985 (64%) English-speaking adults responded to the survey invitation; 5932 owned firearms, including 1933 who had purchased firearms since 2019, of whom 447 had become new gun owners. The estimated number and characteristics of adults who, since 2019, have purchased firearms, distinguishing those who became new gun owners from those who did not, and the estimated number of household members newly exposed to firearms. An estimated 2.9% of U.S. adults (7.5 million) became new gun owners from 1 January 2019 to 26 April 2021. Most (5.4 million) had lived in homes without guns, collectively exposing, in addition to themselves, over 11 million persons to household firearms, including more than 5 million children. Approximately half of all new gun owners were female (50% in 2019 and 47% in 2020 to 2021), 20% were Black (21% in 2019 and in 2020-2021), and 20% were Hispanic (20% in 2019 and 19% in 2020-2021). By contrast, other recent purchasers who were not new gun owners were predominantly male (70%) and White (74%), as were gun owners overall (63% male, 73% White). Retrospective assessment of when respondents purchased firearms. National estimates about new gun owners were based on 447 respondents. Efforts to reduce firearm injury should consider the recent acceleration in firearm purchasing and the characteristics of new gun owners. The Joyce Foundation.